A critical discourse analysis of Jayland Walker's demise in digital journalism - Tengku Firmansyah, Handika Dewa; Degaf, Agwin (Englisia: Journal of Language, Education, and Humanities, 2024)
This research investigates the shooting incident involving Jayland Walker, an African American citizen, on June 27, 2022, resulting from a traffic violation in Akron, United States, and its subsequent coverage across major online media outlets such as CNN News, NBC News, and The Washington Post. Utilizing qualitative methods and drawing on Van Dijk's (1985) Critical Discourse Analysis (CDA) model, the study focuses on analysing the ideologies embedded in ten online news stories from June 2022 to August 2022. The findings highlight a discernible trend in the representation of Jayland Walker by CNN News and The Washington Post, where he is predominantly portrayed as a victim, with the police depicted negatively through strategic use of lexical elements and metaphors, underscoring the influence of media ownership ideologies in shaping news content. In contrast, NBC News maintains a more neutral stance, attributed to frequent changes in ownership. The research contributes theoretically to CDA, providing a conceptual framework for students engaged in critical discourse analysis studies, and offers insights into the complexities of media representation in incidents involving discrimination and police violence.